ANALISIS EFEKTIVITAS DAN ESTIMASI PENERIMAAN PAJAK BPHTB SERTA KONTRIBUSINYA TERHADAP PAD KABUPATEN SUKOHARJO TAHUN 2011-2015 - Esti Wulandari, Fadjar Harimurti & Bambang Widarno (Universitas Slamet Riyadi, 2017)
The purpose of research is to analyze the effectiveness and estimation a taxrevenue of Tax on Acquistion of Land and Building as well as its contribution to thelocal revenue in Sukoharjo regency on 2011 – 2015 year. This research is the casestudy in Sukoharjo regency goverment on 2011 – 2015 year. This research took asecondary data from DPPKAD Sukoharjo regency. Technical analysis of the dataused the analysis of effectiveness, analysis contribution and analysis estimation. Theresults of the analysis effectiveness concluded that the tax BPHTB in 2011 – 2015year had an average effective rate of 138,26%, this shows that a tax revenue BPHTBon 2011 – 2015 year,can said to be effective as a percentage of more than onehundred percent effectiveness. The analysis of contribution a tax BPHTB to the localrevenue in Sukoharjo regency on 2011 – 2015 year had an average contribution rateof 16,15%, this shows that the contribution to the local revenue in Sukoharjo regencyon 2011 – 2015 year is said to to greatly contribute for more than four percentagecontribution percent. While the analysis of tax revenue estimation of BPHTB 2016 –2018 year is more increase everyKeywords: Tax BPHTB, effectiveness, estimates, contributions, local revenue.